SWOT Analysis of Development Strategy Infrastructure in Optimizing Natural Resources in Tamansari Village - Ahmad Saef Alfath; Izzatun Aini Hall (Journal Research of Social Science, Economics, and Management, 2024)
This article aims to analyze the strategy for developing road infrastructure in Tamansari Village using the SWOT analysis approach, in order to formulate the right strategy to increase social and economic growth in the village through better infrastructure development. This study uses a descriptive qualitative method, because in an in-depth understanding of the village situation this method is useful for understanding phenomena in depth through analysis of conditions in the field. The object of this study, namely the development of Tamansari Village Road infrastructure using SWOT Analysis. The types and sources of data used in this study are primary and secondary data. The development of road infrastructure in Tamansari Village aims to improve the economy and quality of life of the community by optimizing the potential of village natural resources. Although the main road is good, some sections still need repair. The main challenges are limited budget and weather. Through SWOT analysis, strengths include community participation and government support, while weaknesses are limited budget and road maintenance problems. Opportunities include economic growth and tourism, while threats include policy changes and worker safety risks. Road infrastructure development in Tamansari Village has the potential to improve accessibility, quality of life, and sustainability of natural resources, as well as support the agriculture, tourism, and MSME sectors. The SWOT analysis shows weaknesses related to budget and human resources, but there are opportunities for economic growth. Suggested solutions include improving budget management, HR training, socialization, road maintenance, and safety risk mitigation.